2015
DOI: 10.1016/j.atherosclerosis.2015.04.809
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of familial hypercholesterolaemia in coronary patients: An analysis of EUROASPIRE IV, a study of the European Society of Cardiology

Abstract: The prevalence of potential FH in coronary patients is high; the results underscore the need to promote identification of FH in CHD patients and to improve their risk factor profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 26 publications
12
93
3
9
Order By: Relevance
“…In Australia 7) , 14.3% of coronary patients aged less than 60 years were found to have phenotypic FH. These data concur with reports from Europe 38) .…”
Section: (2) Epidemiology: Prevalence Of Fh In Community and High-rissupporting
confidence: 93%
“…In Australia 7) , 14.3% of coronary patients aged less than 60 years were found to have phenotypic FH. These data concur with reports from Europe 38) .…”
Section: (2) Epidemiology: Prevalence Of Fh In Community and High-rissupporting
confidence: 93%
“…10) Recently, EU-ROASPIRE IV data also demonstrated that the prevalence of potential FH in patients with acute coronary events was 8.3% (1 in 12), and more in men less than 50 years old (22%). 24) The possible contribution of FH to CAD might be higher even in Japanese because of the low prevalence of CAD among the general Japanese population. However, it is difficult to diagnose heterozygous FH in patients with ACS because of increasing cholesterol catabolism and the fact that they take statins just after the onset of ACS.…”
Section: Discussionmentioning
confidence: 99%
“…‘Effective treatment’ relates to best-practice recommendations advised by European (ESC/EAS) [25,26] and American (ACC/AHA) [27] guidelines of the management of dyslipidaemia to prevent CVD. These unanimously recommend that individuals with a high or very high CVD risk should receive treatment to achieve a reduction in LDL-C levels of 50% or more – a target currently attained by only 3.7% of Bulgarian HeFH patients [28,29]. ETPYs are thus calculated by multiplying the proportion of patients that attain a reduction in LDL-C levels of at least 50% by the predicted survival in each cycle.…”
Section: Methodsmentioning
confidence: 99%